2004
DOI: 10.1126/science.1093087
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Photosynthetic Oxygen-Evolving Center

Abstract: Photosynthesis uses light energy to drive the oxidation of water at an oxygen-evolving catalytic site within photosystem II (PSII). We report the structure of PSII of the cyanobacterium Thermosynechococcus elongatus at 3.5 angstrom resolution. We have assigned most of the amino acid residues of this 650-kilodalton dimeric multisubunit complex and refined the structure to reveal its molecular architecture. Consequently, we are able to describe details of the binding sites for cofactors and propose a structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

172
3,556
14
23

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,203 publications
(3,765 citation statements)
references
References 49 publications
172
3,556
14
23
Order By: Relevance
“…EPR measurements were made in triplicate using a Bruker Elexsys 580 X-band spectrometer and Bruker ER 4116DM dual-mode EPR cavity. The EPR measurements Chart 1: Possible Structural Candidates for the Mn 4 Ca Core of the WOC in PSII Based on Single-Crystal Mn EXAFS (Structures 1-3) or XRD (Structure 4) Studies (9,13) apo-WOC-PSII { \}…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPR measurements were made in triplicate using a Bruker Elexsys 580 X-band spectrometer and Bruker ER 4116DM dual-mode EPR cavity. The EPR measurements Chart 1: Possible Structural Candidates for the Mn 4 Ca Core of the WOC in PSII Based on Single-Crystal Mn EXAFS (Structures 1-3) or XRD (Structure 4) Studies (9,13) apo-WOC-PSII { \}…”
Section: Methodsmentioning
confidence: 99%
“…However, the relative position of Ca 2+ within the Mn 4 O x cluster differs according to which type of data is emphasized and the assumptions of the models used to interpret the raw data. Spectroscopic and XRD data have constrained the possible core topologies to only a few types, with the structures given in Chart 1 proposed on the basis of one or more lines of evidence (9)(10)(11)13). These structural proposals have led to a number of mechanistic proposals for the role of calcium in O 2 evolution reviewed elsewhere (11,(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Ferreira et al (2004) represented the structure of Ca 2+ as part of a cubane with three Mn atoms, and no protein ligands to the metal were shown. In contrast, Loll et al (2005b) proposes the structure of carboxylate oxo anion ligands to Ca 2+ from Glu189 and Ala 334, both of which provide oxo anion ligands to Mn atoms of the cluster (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Loll et al (2005a) examined the effects of Ca 2+ binding on PsbO from T. elongatus and concluded that binding of the metal had inconsequential effects on structure. Murray and Barber (2006) analyzed data in Ferreira et al (2004) and speculate that a Ca 2+ binding site is present in T. elongatus PsbO that is near the lumenal side of PSII. At the same time, all of the currently available models based on crystallographic data (Loll et al 2005b) or on EXAFS results (Yachandra 2005;Yano et al 2006) place the functional Ca 2+ site in the OEC in close proximity to the Mn cluster, and do not predict ligation by amino acid side chain residues of PsbO.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that MSP, located on the luminal surface within PSII, forms an eight-stranded -barrel. The whole protein takes on an elongated shape with two major domains (11). On the basis of this, homologous models for eukaryotic MSP were built by using bioinformatics analysis.…”
mentioning
confidence: 99%